Thematic Cartography for Adaptive Visualization Systems - Evgheni Polisciuc (2021)
Doctoral thesis submitted in partial fulfllment of the Doctoral Program in Information Science and Technology and presented to the Department of Informatics Engineering of the Faculty of Sciences and Technology of the University of Coimbra.